Perbedaan Keparahan Karies Gigi Pada Anak di Sekolah Dasar yang Sudah Melaksanakan UKGS dan Belum Melaksanakan UKGS di Kecamatan Kradenan Tahun 2016 (Observasi pada Anak Sekolah usia 11-12 tahun ) - Pratiwi, Anita Dian, drg. Lasmi Dewi Nurnaini, Sp.KGA (2016)
Background: oral disease happened on 89% Indonesian children under 12 years old. That situation influenced their health status, growth and development also learning. Caries was disease often experienced by elementary students because of their habbit and lack of knowledge. School Dental Health Service (UKGS) was one of attempt which play roles to prevent oral diseases. UKGS provided services in the form of enhancement or promotion,prevention or preventive, treatment or curative and recovery or rehabilitative. Purpose: this study aimed was to know the difference of caries severity among student in elementary school who implementing UKGS and elementary schools who have not implementing UKGS. Method: this research was analytic observational study using cross sectional. Samples was 87 student who their school have not implementing UKGS and 83 student who their school implementing UKGS by the age 11-12 years old. Samples was taken in elementary school at Kradenan district using stratified random sampling. Caries severity was measured using caries severity index (CSI). Data of the research was analyzed using independent t-test. Data are not normally distributed, then followed by Mann-Whitney test alternative. Result: results showed that student of elementary school who implementing UKGS, the CSI score was 3,684 which included mild category, while student of elementary school who have not implementing UKGS the CSI score was 7,1255 which included moderate category. Mann-Whitney test results used confidence level 95% p value = 0.000 (p <0.05). Conclusion: which means there were significant differences scores among student of elementary school who implementing UKGS and student who have not implementing UKGS. Student of elementary school who implementing UKGS has lower caries severity than student of elementary school who have not implementing UKGS in Kradenan district.